The Existence of Fixed Points for Nonlinear Contractive Maps in Metric Spaces with 𝑤-Distances - Hossein Lakzian; Ing-Jer Lin (Journal of Applied Mathematics)
Some fixed point theorems for (𝜑,𝜓,𝑝)-contractive maps and (𝜑,𝑘,𝑝)-contractive maps on a complete metric space are proved. Presented fixed point theorems generalize many results existing in the literature.